Influence of thermophysical properties of working fluid on the design of cryogenic turboexpanders using nsds diagram. Issue 1 (November 2015) - Sam, Ashish A; Ghosh, Parthasarathi
Abstract: Cryogenic turboexpanders are an essential part of liquefaction and refrigeration plants. The thermodynamic efficiency of these plants depends upon the efficiency of the turboexpander, which is the main cold generating component of these plants, and therefore, they should be designed for high thermodynamic efficiencies. Balje's [1] ns ds chart, which is a contour of isentropic efficiencies plotted against specific speed and specific diameter, is commonly used for the preliminary design of cryogenic turboexpanders. But, these charts were developed based on calculations for a specific heat ratio (γ) of 1.4, and studies show that care should be taken while implementing the same for gases which have a higher γ of 1.67. Hence there is a need to investigate the extent of applicability of ns ds diagram in designing expansion turbines for higher specific heat ratios. In this paper, Computational Fluid Dynamics (CFD) analysis of cryogenic turboexpanders was carried out using Ansys CFX®. The turboexpanders were designed based on the methodologies prescribed by Kun and Sentz [2] following the ns ds diagram of Balje and Hasselgruber's technique for generating blade profile. The computational results of the two cases were analysed to investigate the applicability of Balje's ns ds diagram for the design of turboexpanders for refrigeration and liquefaction cycles.